CORPORATE SOCIAL RESPONSIBILITY AWARENESS AND ATTITUDES IN CHINESE FOUNDED COMPANIES IN MALAYSIA - Lai, Yu Jen (2006)
This dissertation explores the CSR awareness and attitudes of Chinese founded companies in Malaysia. Various authors have provided insights CSR in Malaysia but none have written specifically about CSR in Chinese founded companies and their commitment towards charitable causes and other community-based projects as part of their heritage and culture as Overseas Chinese. Upon asking whether Chinese founded companies operating in Malaysia are aware of and commit to CSR and if so what activities and what their motivations for CSR are in the Chinese Malaysian context, the author submits that they practice a form of explicit and community-based CSR. In exploring this phenomena, this dissertation is not another addition to the shelf of dissertations in the Nottingham University Business School Library that merely fulfils the requirement for completing a Master's programme, but this dissertation is determined to unravel insights on CSR in Chinese founded companies in Malaysia; a new concept within an age old tradition of philanthropy amongst Overseas Chinese businessmen.